(untitled) (International Journal of Food and Nutritional Sciences, 2022)
An isocratic reversed phase stability-indicating high performance liquid chromatographic (HPLC) assay method was developed and validated for quantitative determination of Zopiclone in bulk drugs. Zopiclone is a non-benzodiazepine compound and its mechanism of action based on modulating benzodiazepine receptors.